Pengaruh Penggunaan E-magazine Terhadap Hasil Belajar Materi Keanekaragaman Hayati Untuk Mendukung Program SDGs di SMP Negeri 2 Samarinda - Shuhaila, Chintya Rofidah; Nasution, Ruqoyyah; Jailani, Jailani; Herliani, Herliani; Akhmad, Akhmad; Rosita, Dewi (Symbiotic: Journal of Biological Education and Science, 2025)
The low level of students’ understanding in the learning process is often caused by limited variations in instructional media, posing a challenge to achieving SDG 4 on quality education. This study aimed to examine the effect of e-magazine learning media on students’ learning outcomes in biodiversity topics at SMP Negeri 2 Samarinda, as part of supporting the SDGs program. A quantitative approach with a quasi-experimental design of the pretest-posttest control group type was used. Sampling was conducted using purposive sampling, and data were collected through tests and questionnaires assessing cognitive, affective, and psychomotor domains. Data were analyzed using an independent sample t-test and N-gain. The results showed that the experimental class achieved higher learning outcomes than the control class. The average cognitive score was 81 in the experimental group and 72 in the control group. In the affective and psychomotor domains, the experimental class achieved 82% and 81%, respectively, categorized as good, while the control class achieved 75% (sufficient) in both domains. These findings indicate a significant improvement in the cognitive domain (Ha accepted, H₀ rejected) and a positive impact on affective and psychomotor outcomes. Thus, e-magazine media effectively supports technology-based learning aligned with SDGs goals.